Pengaruh Literasi Media terhadap Perilaku Penyebaran Hoax di Kalangan Generasi Z - Kamilatus Sya'diyah; Rosita Anggraini (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
This research is to determine the effect of media literacy on the behavior of spreading hoax. The concept used is the concept of media literacy, which consists of seven skills, and Hoax Spreading Behavior, which consists of three factors. This research approach is quantitative. The research method used is an explanatory research type survey. The research population in this study were 87 of STIKOM Inter Studi Students, Broadcasting Department, Class 2017. To calculate the number of samples, used the Slovin formula with an error rate of 10% and got the results of 57 people as respondents. Data collection is observation, questionnaire distribution, and literature study. The data obtained were analyzed by statistical calculations using the SPSS program. The results show that the media literacy variable (X) had a significant influence to the hoax spread behavior variable (Y) in Generation Z. However, respondents tend to have media literacy skills at a basic level, because they only has an effect of 32%. Thus, this is a reminder that the public can increase awareness in media literacy regarding the spread of hoaxes around them.